2007
DOI: 10.1007/s10964-007-9171-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HIV Risks among Gay, Lesbian, Bisexual and Heterosexual Homeless Youth

Abstract: Youth who are homeless and gay, lesbian or bisexual (GLB) are one of the most disenfranchised and marginalized groups in our society. The purpose of this study is to examine and compare HIV in GLB homeless youth with their heterosexual counterparts. Participants for this study included 268 youth involved in treatment outcome studies with substance abusing homeless youth. Results suggest that GLB youth have greater HIV risks and that these risks are greater among bisexual females. In examining the predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 50 publications
4
87
2
1
Order By: Relevance
“…As a result, these groups more frequently report sexual abuse, violence, discrimination, drug and alcohol use, and exchange of sex for money and favors. 6,9,14,21,22,26 Among homosexuals, homophobia has been identifi ed as the main factor driving them onto streets. 4.19 A qualitative study conducted in Los Angeles 21 showed that women's choice to use condoms is strongly affected by their emotional involvement and trust in their partner, and that sex occur due to various reasons including sexual abuse and need for affective involvement.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these groups more frequently report sexual abuse, violence, discrimination, drug and alcohol use, and exchange of sex for money and favors. 6,9,14,21,22,26 Among homosexuals, homophobia has been identifi ed as the main factor driving them onto streets. 4.19 A qualitative study conducted in Los Angeles 21 showed that women's choice to use condoms is strongly affected by their emotional involvement and trust in their partner, and that sex occur due to various reasons including sexual abuse and need for affective involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The youth who are disproportionately targeted and victimized are frequently members of non-dominant social identity categories, such as Black and Latina girls (Farley et al 2017). Additionally, while most sexually exploited youth are cisgender, heterosexual females, other groups such as sexual minority youth-particularly transgender youth-are at very high risk of being exploited (Gangamma et al 2008;Wilson et al 2009). …”
Section: Structural Inequities and Domestic Minor Sex Traffickingmentioning
confidence: 99%
“…Primarily, the risks that lesbian, gay, and bisexual (LGB) homeless youth face on the street are significantly exacerbated by their sexual orientation status (Gattis, 2013;Van Leeuwen et al, 2006). LGB-identified homeless youth engage in more survival sex in exchange for food, shelter, or other essentials (Gangamma, Slesnick, Toviessi, & Serovich, 2008) and experience more street victimization compared to their heterosexual counterparts (Tyler, 2008).…”
Section: Runaway and Homeless Lgbt Youthmentioning
confidence: 99%